EU Citizenship and Social Rights 2018
DOI: 10.4337/9781788112710.00008
|View full text |Cite
|
Sign up to set email alerts
|

Intra-EU migration and social rights: an introduction

Abstract: Marshall (1950) conceptualizes citizenship as a status of membership in a community; social rights are defined as core for the ability of all citizens, irrespective of class, to more fully enjoy political and civil rights. According to Marshall, social rights encompass everything from the right to a modicum of economic welfare to the right to live the life of a civilized being according to the standards prevailing in the society. The evolution of social rights, and of the welfare state more generally, was clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The most advanced scheme in this regard is the EU social security coordination. Together with the extensive jurisprudence of the Court of Justice of the EU, the EU coordination often guarantees that mobile EU citizens have an easier access to social benefits compared to TCNs, while also limiting states' margin of manoeuvre in freely regulating EU migrants' access to welfare (Seeleib-Kaiser and Pennings 2018;Schmidt et al 2018).…”
Section: Challenging the Welfare State In An Era Of Internationalmentioning
confidence: 99%
“…The most advanced scheme in this regard is the EU social security coordination. Together with the extensive jurisprudence of the Court of Justice of the EU, the EU coordination often guarantees that mobile EU citizens have an easier access to social benefits compared to TCNs, while also limiting states' margin of manoeuvre in freely regulating EU migrants' access to welfare (Seeleib-Kaiser and Pennings 2018;Schmidt et al 2018).…”
Section: Challenging the Welfare State In An Era Of Internationalmentioning
confidence: 99%
“…In an increasingly mobile world, the organisation of social security faces new challenges (Sabates-Wheeler, Koettl, & Avato, 2011). Additionally, migrants within the EU-where a unique transnational social security system has been established-face substantial barriers when accessing welfare-related services and resources (Scheibelhofer & Holzinger, 2018;Seeleib-Kaiser & Pennings, 2018). For example, studies from Germany and Austria have shown that the enforcement of German as the language of administration and communication is the main informal barrier in this regard (Holzinger, 2020;Ratzmann, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Another tension of particular relevance in the context of the EU concerns the multilevel governance of social rights: While European integration has gradually restricted the authority of EU member states to delimit granting social rights to other EU citizens, the organisation of social security still relies on national institutions to design and provide social benefits (Seeleib-Kaiser and Pennings 2018). The organisation of social security, traditionally located within the sovereignty of the nation state, generally faces new challenges in an increasingly mobile world (Sabates-Wheeler, Koettl, and Avato 2011).…”
Section: Introductionmentioning
confidence: 99%
“…When analysing social security rights from a sociological perspective, not only must normative as well as a political-legal registers be considered, but also practical elements that encompass the mechanisms of institutional implementation and the actual experiences of access (Carmel 2013;Marshall 1977;Soysal 2012). While the EU has indeed created a unique transnational portability system to secure the social security rights of mobile Europeans, substantial access barriers still persist in practice (Scheibelhofer, Holzinger, and Regös forthcoming;Seeleib-Kaiser and Pennings 2018). A recent study of EU migrants' access to subsistence support in Germany has shown that the main informal barrier in this respect is the enforcement of German as the language of administration and communication (Ratzmann 2018).…”
Section: Introductionmentioning
confidence: 99%